2007
DOI: 10.1121/1.2749452
|View full text |Cite
|
Sign up to set email alerts
|

Blue and fin whale call source levels and propagation range in the Southern Ocean

Abstract: Blue ͑Balaenoptera musculus͒ and fin whales ͑B. physalus͒ produce high-intensity, low-frequency calls, which probably function for communication during mating and feeding. The source levels of blue and fin whale calls off the Western Antarctic Peninsula were calculated using recordings made with calibrated, bottom-moored hydrophones. Blue whales were located up to a range of 200 km using hyperbolic localization and time difference of arrival. The distance to fin whales, estimated using multipath arrivals of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
165
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(177 citation statements)
references
References 33 publications
10
165
1
1
Order By: Relevance
“…A model developed by Tennessen and Parks (2016) demonstrated that a right whale is not able to hear an upcall from another whale if a ship passes at less than 25 Km, unless the calling whale increases the amplitude of the calls by 20 dB. Despite differences in call source levels between right whales and blue, fin and sei whales, they share similarities in call frequency ranges (e.g., Parks and Tyack, 2005;Sirović et al, 2007;Romagosa et al, 2015). Detection ranges of calls for these three species might be affected by passing ships in similar ways, which is of concern given the dependence of Balaenoperids on long range communication (Payne and Webb, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…A model developed by Tennessen and Parks (2016) demonstrated that a right whale is not able to hear an upcall from another whale if a ship passes at less than 25 Km, unless the calling whale increases the amplitude of the calls by 20 dB. Despite differences in call source levels between right whales and blue, fin and sei whales, they share similarities in call frequency ranges (e.g., Parks and Tyack, 2005;Sirović et al, 2007;Romagosa et al, 2015). Detection ranges of calls for these three species might be affected by passing ships in similar ways, which is of concern given the dependence of Balaenoperids on long range communication (Payne and Webb, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of such PAM systems, is the continuous mapping of presence and distribution of whales over ocean basins (e.g. Greene et al, 2004;Sirovic et al, 2007;Stafford et al, 2007;Mas et al, 2008) and assessing their densities, (e.g. Ko et al, 1986;McDonald and Fox, 1999;Clark and Ellison, 2000), sometimes in quasi real-time (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic signal source level, propagation loss, and local background noise levels determine detection ranges (c.f. Sirovic et al, 2007;Stafford et al, 2007;Simard et al, 2008). Moreover, cetacean sounds vary considerably in time-frequency, from infrasonic calls of baleen whales to ultrasonic clicks of toothed whales, and in amplitudes among species and within a species' vocal repertoire (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Vocalization source level is also essential for determining marine mammal communication ranges, which are key considerations in assessing the impact of anthropogenic sound on marine mammal behavior [31,32]. Previous estimates of vocalization source level for the baleen whale species considered here include fin whales off the Western Antarctic Peninsula and near Juan de Fuca Ridge of the northeast Pacific Ocean [33,34]; sei whales on the continental shelf off New Jersey [35]; minke whales near the Great Barrier Reef, Hawaii, and the Stellwagen Bank area of the Gulf of Maine [28,36,37]; and blue whales distributed in multiple ocean areas, including both the Pacific and Atlantic Ocean [15,33,[38][39][40]. Previous vocalization source level estimates typically focused on a single species based on vocalization sample sizes ranging from a few tens to a few hundred.…”
Section: Introductionmentioning
confidence: 99%
“…Previous vocalization source level estimates typically focused on a single species based on vocalization sample sizes ranging from a few tens to a few hundred. Transmission losses TL were often modeled previously using the azimuthally-symmetric formula TL = X log 10 R with the transmission loss coefficient X varying between the limits of spherical spreading (X = 20) and cylindrical spreading (X = 10) for source-receiver range separation R depending on the environment [15,33,36,37]. In [35], a normal-mode based ocean acoustic propagation model was employed to correct for transmission losses in estimating sei whale vocalization source level in the shallow New Jersey shelf environment.…”
Section: Introductionmentioning
confidence: 99%